Projovem trabalhador no Município de Serra-ES : análise de concepções, ações e políticas sociais para a juventude - Lanes, Mônica Paulino de (2013)
This dissertation aims to analyze the program Projovem Worker Serra-ES identifying conceptions of youth present, seeking to capture whether these conceptions influence the actions of the program in the city. For this work began with a discussion of the historical and current settings on social policies, especially of youth policies in Brazil. We also performed a literature search about the conceptions youth since the 1950s seeking to confront the social category of youth broadly. To identify the concepts in the municipality conducted interviews with the crew that runs the program, as well as documentary research. The results indicate that despite advances in youth policies there are aspects that still need to be overcome such as fragmentation, overlap of public actions, the lack of administrative, insufficient budget, lack of concern with research and not construction of social indicators solid; being extremely necessary and urgent to open channels of dialogue with youth in order to build a policy that represents the interests of youth. Identified, further, that the program is an expression synthesis of social policies - decentralization, privatization and focusing. With regard to the concepts of youth in the program ProJovem Worker Sierra realized that still stands the perception of youth as a symptom of social problems as a result of the context in which the program operates.